PENGARUH E-BUDGETING, PENGENDALIAN INTERNAL, DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN - Y, Idham Novendri (Jurnal Akuntansi, 2024)
This research aims to find out whether e-budgeting, internal control, and regional financial accounting systems have an effect on financial management accountability in Bulungan district regional apparatus organizations. This research uses a quantitative method, namely by presenting research results in the form of numbers which are then explained and interpreted in a description, in order to test the hypothesis. The subjects of this research are the parties involved in preparing regional financial reports for each OPD in Bulungan Regency. The data used in this research is primary data obtained from respondents who filled out the questionnaire. The sample in this research was 60 taken using the purposive sampling method. The tool used for this research uses multiple linear regression analysis. The test results stated that the variables e-budgeting, internal control had no effect on regional financial management accountability, while the regional financial accounting system had an effect on regional financial management accountability in the Bulungan Regency OPD.